Model For Learning Conflict Resolution Education Through Approaches To 12 Peace Value - Putra, Fajar Setyaning Dwi; Winarti, Agus (Technium Education and Humanities, 2023)
The inheritance of conflicts in social, cultural and religious systems, which is inherited from an early age, is one of the factors causing hatred towards certain ethnicities, ethnicities and religions that are fostered from an early age to adulthood. The need for an understanding of the value of diversity and diversity is a key factor in building future generations of peace. These values of peace need to be taught in the formal education system at every level of education which is integrated through the Pancasila and Citizenship Education subjects. Through the values of peace a person is able to understand differences both physically, culturally and thoughtfully. This research takes the subject of the Peace Generation Indonesia community who have conducted training for trainers as agents of peace about learning models of 12 values of peace. The 12 values of peace taught are 1. Acceptance, 2. Prejudice, 3. Sukuism, 4. Religious Differences, 5. Sex Gender Differences, 6. Economic Status Differences, 7. Group / Gang Differences, 8. Understanding Diversity, 9 Understanding Conflict, 10. Refusing Violence, 11. Recognizing Mistakes, 12. Apologizing.